2016
DOI: 10.1038/nmeth.4068
|View full text |Cite
|
Sign up to set email alerts
|

Robust statistical modeling improves sensitivity of high-throughput RNA structure probing experiments

Abstract: Structure probing coupled with high-throughput sequencing could revolutionize our understanding of the role of RNA structure in regulation of gene expression. Despite recent technological advances, intrinsic noise and high sequence coverage requirements greatly limit the applicability of these techniques. Here we describe a probabilistic modeling pipeline that accounts for biological variability and biases in the data, yielding statistically interpretable scores for the probability of nucleotide modification t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 37 publications
0
42
1
Order By: Relevance
“…Then we predicted secondary structures of yeast 18S and 25S rRNAs for each method and evaluated the predicted structures using commonly accepted measures such as sensitivity and positive predictive value (PPV) (Sloma and Mathews, 2015). In this evaluation (Figure 2C), as well as in a comparison (Table S4) with BUM-HMM (Selega et al, 2017), PROBer’s performance was superior to the alternative approaches. In addition, we have demonstrated that PROBer is robust to priming biases with respect to modification probability estimation (Figure S10 and S11).…”
Section: Resultsmentioning
confidence: 80%
“…Then we predicted secondary structures of yeast 18S and 25S rRNAs for each method and evaluated the predicted structures using commonly accepted measures such as sensitivity and positive predictive value (PPV) (Sloma and Mathews, 2015). In this evaluation (Figure 2C), as well as in a comparison (Table S4) with BUM-HMM (Selega et al, 2017), PROBer’s performance was superior to the alternative approaches. In addition, we have demonstrated that PROBer is robust to priming biases with respect to modification probability estimation (Figure S10 and S11).…”
Section: Resultsmentioning
confidence: 80%
“…Of note, robust statistical assessment of reactivity from biological replicates is generally lacking, with only a few data analysis pipelines able to return statistically significant sites based on biological replicates (Choudhary, Ruan, Deng, Shih, & Aviran, 2017;Talkish et al, 2014). Recently, a sophisticated Beta-uniform mixture hidden Markov Model (BUM-HMM) machine learning pipeline was developed to deal with biological variability and biases in the chemical probing datasets obtained from NGS experiments (Selega et al, 2017). Furthermore, a similar statistical model has been used to predict small RNA motifs from noisy structural probing data (Ledda & Aviran, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Aviran et al, ; Talkish et al, ; Tang et al, ; Busan and Weeks, ; Selega, Sirocchi, Iosub, Granneman, and Sanguinetti, ; Ledda and Aviran, ; Li and Aviran, …”
Section: Challenges and Potential Pitfallsmentioning
confidence: 99%
“…Alternatively, reactivities have been estimated as odds ratio of experiment to control detection rates [35]. To control the range of reactivities, others take the logarithm of the odds ratio [30,31,36,55,81]. Occasionally, detection rates in experiment are found to be less than their counterparts in control.…”
Section: Estimation Of Structural Profilementioning
confidence: 99%
“…Another extension of the said statistical modeling work on SHAPE-Seq has been recently published by Selega et al . [81]. This method scores significance of modification levels from stop counts and nucleotide-level coverages under an assumption that modification states do not randomly switch, i.e., significantly reactive/unreactive nucleotides tend to appear in continuous stretches.…”
Section: Estimation Of Structural Profilementioning
confidence: 99%